UNA LECTURA CONJUNTA DEL PRIMER ENCOMIO A CONSTANCIO Y EL ENCOMIO A EUSEBIA DE JULIANO - García Ruiz, Mª Pilar (Exemplaria Classica, 2015)
This contribution analyses Julian’s First Panegyric in honour of Constantius and the Panegyric in Honour of Eusebia as complementary texts. The presence of a shared reference to the eulogy based on virtues; a particular meaning of ??????? and ??????? have led to conclude that, these speeches constituted a double ???????, suitable either for who deserve it or not. Mordant commentaries on Constantius in both panegyrics and some other structural arguments support the thesis that the speeches would have been rewritten subsequently.